Pengaruh Shopping Lifestyle, Online Store Beliefs, dan Flash Sale Terhadap Impulse Buying Produk Skintific pada Pengguna Shopee di Surabaya - Ade Rishna Hidayah Shafira Buchori; Izah Bana Murtazah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Impulse buying is a form of quick reaction without any planning to decide to shop. This study aims to determine the effect of Shopping Lifestyle, Online Store Beliefs, and Flash Sales on impulse buying. Sampling used a purposive sampling method. Data collection was carried out through a questionnaire measured with a Likert scale. The data analysis test used in this study refers to the multiple linear regression test. Based on the results of the research that has been conducted, it can be concluded that the three variables simultaneously have a significant effect on Impulse Buying. The Shopping Lifestyle and Flash Sale variables partially have a significant positive effect on impulse buying, while the Online Store Beliefs variable partially has no significant effect on Impulse Buying.